Penerapan Metode Bermain Peran terhadap Keterampilan Berbicara pada Materi Cerita Fantasi Siswa Kelas VII MTS Bustanul Huda Kota Pasuruan - Yaftahillah Yaftahillah; Ilmiyatur Rosidah; Badriyah Wulandari (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This study aims to apply the role-playing method in speaking skills to students on fantasy story text material in Indonesian language lessons. Students carry out learning activities using the role-playing method. This learning method is a learning method that is applied in classroom learning. Most teachers in the past used a lecture model in providing material which could make students feel bored and not focused on receiving the material given by the teacher. This study examines students' speaking skills in mastering fantasy story text material using the role-playing method. Researchers focus on students' speaking skills so that they can better understand the meaning of fantasy story texts. This research was conducted at MTS Bustanul Huda, Pasuruan City using data in the form of subjects and objects. The subjects of the study were grade VII students and the object used was the role-playing method. The method used was qualitative description, using data collection procedures including observation and documentation. The results of applying the role-playing method in speaking skills on fantasy story text material can produce an understanding that is in accordance with the material using the role-playing method. From the activities that have been carried out, the results were obtained regarding understanding the material and speaking skills in role-playing.